Hot deformation behavior and dynamic recrystallization constitutive modeling of Al–Cu–Mg powder compacts processed by extrusion at elevated temperatures. (March 2021) - Bharath, Katti; Khanra, Asit Kumar; Davidson, MJ
The deformation behavior of Al–Cu–Mg sintered preforms has been investigated by extrusion in the temperature range of 450–550°C and strain rate range of 0.1–0.3 s −1, respectively. The aim of this study is to analyze the effect of initial preform relative density on the hot deformation behavior and to model and predict the flow stress of extruded samples using constitutive equations. The true stress–strain curves exhibit three stages of deformation, which represent work hardening, dynamic recovery, and dynamic recrystallization during deformation at different temperatures, strain rates, and initial preform relative densities of 70%, 80%, and 90%, respectively. The results show that the flow stress values are influenced by initial preform relative density, deformation temperature, and strain rate. Microstructural examination of extruded specimens has been performed by optical microscopy and scanning electron microscopy. Arrhenius-type constitutive equations are developed to predict the flow stress of hot-extruded powder metallurgy processed aluminum alloy (Al–4%Cu–0.5%Mg). Zener–Hollomon parameter is used to explain the relationship between peak flow stress, temperature, and strain rate in an exponential equation containing the deformation activation energy and material constants. Subsequently, the statistical indicators correlation coefficient ( R ) and the average absolute relative error are assessed to confirm the validity of constitutive equations. The results indicate the experimental and predicted peak flow stress values are in good agreement, which indicate the accuracy and reliability of the developed model for powder metallurgy processed Al–4%Cu–0.5%Mg preforms.